DISCRETE ORTHOGONALITY FOR OFDM/OQAM - B. Vishal Raja Zacharias, Dr. Anupama Deshpande (International Journal of Advanced Science and Technology, 2020)
Multicarrier communication is the basic technology for 4G and upcoming 5G communications. OFDM is the prevailing technology in 4G and FBMC is the dominant contender for 5G technology. This paper gives the drawbacks of existing 4G technology and how it can be avoided using FBMC. OFDM and FBMC are compared in various performances like Spectral efficacy, Power spectral density and computational complexity. Matlab simulations are performed and presented in this paper